2016
DOI: 10.1007/s12155-016-9760-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Blue Agave Bagasse (BAB) as Raw Material for Bioethanol Production Processes by Gravimetric, Thermal, Chromatographic, X-ray Diffraction, Microscopy, and Laser Light Scattering Techniques

Abstract: A detailed characterization of the main types of blue agave bagasse (BAB) obtained from the four largest tequila factories in the State of Jalisco (Mexico) is presented here. After milling/sieving the agave bagasses, two particle size fractions were identified, one rich in fibers and the other consisting of dust/fine particles. Both fractions were analyzed to determine the content of cellulose, hemicellulose, lignin, organic-soluble compounds, absorbed remaining sugars, minerals, and organic matter. After deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…It is useful for the determination of energy content of biomasses and economic analyses, which may aid in determining the efficient use of feedstocks. The HHV for BAB is ∼18 MJ kg –1 , which is similar to dry wood . In a previous contribution from our group we extensively characterized BAB and found that its content of lignin, hemicelluloses, and cellulose are 18.4, 17, and 38.9 wt %, respectively. , These composition results agree well with other results reported in the literature: 16–21 wt % lignin, 17–20 wt % hemicellulose, and 30–35 wt % cellulose…”
Section: Introductionsupporting
confidence: 88%
“…It is useful for the determination of energy content of biomasses and economic analyses, which may aid in determining the efficient use of feedstocks. The HHV for BAB is ∼18 MJ kg –1 , which is similar to dry wood . In a previous contribution from our group we extensively characterized BAB and found that its content of lignin, hemicelluloses, and cellulose are 18.4, 17, and 38.9 wt %, respectively. , These composition results agree well with other results reported in the literature: 16–21 wt % lignin, 17–20 wt % hemicellulose, and 30–35 wt % cellulose…”
Section: Introductionsupporting
confidence: 88%
“…Other experimentally‐guided studies from our group aimed at producing improved saccharification yields have been reported elsewhere. [ 37,40,49,86 ]…”
Section: Resultsmentioning
confidence: 99%
“…Other experimentally-guided studies from our group aimed at producing improved saccharification yields have been reported elsewhere. [37,40,49,86] The different zones and the relationships among length, number of elements, and residence time are shown in Figure 3. As expected, these relationships are linear.…”
Section: Extruder Configuration and Experimental Planmentioning
confidence: 99%
See 1 more Smart Citation
“…Hernández-Meléndez et al [15] describe the characterization of different types of blue agave bagasse from large-scale processing in the tequila industry. This biomass was pretreated using an alkaline extrusion process and subsequent enzymatic hydrolysis under moderate conditions.…”
mentioning
confidence: 99%